The effects of material type, salivary contamination and adhesive application on the performance of pit and fissure sealants - Adem Gok; Kubra Bilge; Tuba Gok (PLoS ONE, 2026)
This study aimed to assess the effects of sealant material type, adhesive application and saliva contamination on the microleakage, shear bond strength (SBS), and interfacial adaptation of pit and fissure sealants. A total of 160 extracted human molars were assigned to eight groups according to sealant type (resin-based, glass ionomer-based, or flowable composite), adhesive application, and contamination condition. Microleakage and unfilled areas at the enamel–sealant interface were assessed by dye penetration and image analysis software after thermocycling. SBS was measured using a universal testing machine, and failure modes were categorized under a stereomicroscope. Interfacial adaptation was analyzed using scanning electron microscopy (SEM). Data were analyzed with Fisher’s exact, Kruskal–Wallis, Mann–Whitney U, and ANOVA tests (α = 0.05). Resin-based and flowable composite sealants exhibited significantly lower microleakage and higher SBS than glass ionomer-based materials (p < 0.05). Adhesive application enhanced SBS but slightly increased microleakage. Saliva contamination markedly reduced bond strength and increased leakage, whereas re-etching effectively restored enamel receptivity and sealing ability. SEM images revealed better adaptation and continuous margins in resin-based and flowable composites, whereas contaminated groups exhibited irregular interfaces and micro gaps. Sealant performance is strongly influenced by material viscosity, surface pretreatment, and contamination control. Re-etching after contamination restores enamel-bonding potential, while adhesive-assisted flowable composites achieve the best combination of sealing, retention, and interfacial adaptation, suggesting their clinical advantage in moisture-compromised environments.